The Omicron variant of concern: The genomics, diagnostics, and clinical characteristics in children - Setiabudi, Djatnika; Sribudiani, Yunia; Hermawan, Kartika; Andriyoko, Basti; Nataprawira, Heda Melinda (Frontiers in Pediatrics, 2022)
Since WHO announced the COVID-19 pandemic in March 2020, SARS-CoV-2 has undergone several mutations, with the most recent variant first identified in South Africa in November 2021, the SARS-CoV-2 variant of concern (VOC B.1.1.529) named by WHO as Omicron. To date, it has undergone more mutations compared to previous SARS-CoV-2 variants, particularly in the S gene that encodes the spike protein, which can cause S gene target failure in some PCR kits. Since its discovery, the Omicron variant has caused a sharp rise in COVID-19 cases worldwide and was responsible for a record 15 million new COVID-19 cases reported globally in a single week, although this may be an underestimate. Since January 2022, Omicron subvariants with variable genetic characteristics, BA.1, BA.1.1, BA.2, BA.3, BA.4, BA.5 and BA.2.12.2 have been identified, with several countries reporting BA.1.1 was the major subvariant (27.42%), followed by BA.2 (25.19%). At the begining of May 2022, BA.2.12.1 mostly (42%) was detected in USA. Like adults, the clinical manifestations of the Omicron variant in children are similar to previous variants consisting of fever, cough, vomiting, breathing difficulties, and diarrhea, with some reports on croup-like symptoms and seizures. Though it presents apparently milder disease than the Delta variant, it is significantly more contagious and has caused more hospitalizations, especially in unvaccinated children under 5 years old and unvaccinated or incompletely vaccinated adults. However, there is insufficient evidence yet to distinguish the Omicron variant from the other variants solely based on clinical manifestations, therefore this review presents a brief literature review of the most current evidence and data related to Omicron.